(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The major drawback of oral drug delivery is inadequate concentration of active pharmaceutical ingredients in systemic circulations. The study set out to design and test matrix tablets containing Ketorolac tromethamine (KT) nanoparticles for sustained activity. The goal of this research was to create a sustained-release medication delivery system using a tablet matrix composed of KT nanoparticles and to analyse its performance. The nanoparticles loaded with KT were further compressed into matrix tablets in this investigation. They were developed by using factorial design to optimize the specific concentrations of drug and polymers. The KT loaded nanoparticles were formulated by employing combined method i.e. Nano precipitation and probe sonication method. The matrix tablets of KT nanoparticles were developed by wet granulation method. KT nanoparticles were discovered to have a particle size range of 199-441 nm and 17.07 ± 0.09 to 22.43 ± 0.23 mv, respectively. Moreover, all the formulations were produced poly dispersibility index (PDI) in optimum ranges. In vitro drug release through nanoparticles were provides sustained action up to 8 hrs. KT nanoparticles loaded matrix tablets showed characteristics of delayed drug release.